The Law of Health and Underage Marriage in the Transcendental Perspective - Widihartati Setiasih; Khudzaifah Dimyati; Absori Absori; Wafda Vivid Izziyana (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Underage marriage is deemed to be a serious problem as brings controversies. Indonesia is one of the countries in the world with a high rate of underage marriage. The health impacts of this dangerous traditional practice include the increase of the mother and baby death rate, and also the rate of reproductive health diseases. The method in this research is the qualitative method. The underage marriage still happens often as there is a high tolerance given by the Constitution of Marriage, which gives the minimum age of 16 years for marriage. There needs to be an effort of harmonization between the various systems of marriage laws which apply in Indonesia so that the legislative challenges which happen becauses of the constitutional regulations’ disparity regarding the underage marriage may be solved. Revisions of the Constitution of Marriage and the Maturity of Marriage Age are proposed as part of the effort to prevent underage marriage. Viewed from the aspect of reproductive health, underage child marriage poses much risks and dangers because physically and mentally, children are not ready to give birth, so it may cause diseases in the reproductive system, and it may even lead to the death of the baby and child. There needs to be the government’s commitment to stop the dangerous traditional practices which affect the health of women and children and ratify the regulations related to their protection. The socialization of the reproductive health and sex education for teenagers must be done intensively by integrating it in the study curriculum at school. Keywords: Health law, Underage marriage, Transcendental.